2019
DOI: 10.1177/0267659119868062
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine extraction by the extracorporeal membrane oxygenation circuit: results from an in vitro study

Abstract: Background: Dexmedetomidine is a sedative administered to minimize distress and decrease the risk of life threatening complications in children supported with extracorporeal membrane oxygenation. The extracorporeal membrane oxygenation circuit can extract drug and decrease drug exposure, placing the patient at risk of therapeutic failure. Objective: To determine the extraction of dexmedetomidine by the extracorporeal membrane oxygenation circuit. Materials and methods: Dexmedetomidine was studied in three clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…21 A recent study at a therapeutically relevant concentration (~600 pg/ml), showed lower sequestration of DEX after 4 hours in ECMO circuits. 8 Another important finding of the current study is the increase (12.1 ± 4.25%, p < 0.05) of DEX concentrations post-MUF (in 19 of 23 circuits). Modified ultrafiltration allows hemoconcentration after weaning from bypass and it has been reported to often alter the plasma concentrations of drugs in ECMO circuits.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…21 A recent study at a therapeutically relevant concentration (~600 pg/ml), showed lower sequestration of DEX after 4 hours in ECMO circuits. 8 Another important finding of the current study is the increase (12.1 ± 4.25%, p < 0.05) of DEX concentrations post-MUF (in 19 of 23 circuits). Modified ultrafiltration allows hemoconcentration after weaning from bypass and it has been reported to often alter the plasma concentrations of drugs in ECMO circuits.…”
Section: Discussionsupporting
confidence: 51%
“…[4][5][6]13,15,16 Several studies investigated the sequestration of DEX in ECMO circuits. 7,8,17 A previous study 7 showed that DEX concentration decreased by 59-73% in the first hour and then continued to decline with a loss of 67-93% of the DEX over 24 hours. 11 Another recent study evaluated the sequestration of DEX in an ex vivo infant ECMO circuit utilizing polymethylpentene membrane oxygenator with protein-bounded PVC tubing and showed sequestration of 51% DEX in 24 hours.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations